solve the quadriatic equation using the quaratic formula, no matter how it is done it comes up wrong and nothing is working

3x^{2} + 2x - 16 = 0

a = 3

b = 2

c = -16

x = [-b ± √(b^{2} - 4ac)]/2a

b^{2} - 4ac = 4 - (4*3*-16) = 196

x = (-2 ± √196)/6

**x = (-2 + 14)/6 = 12/6 = 2**

**x = (-2 - 14)/6 = -16/6 = -8/3**

Check your solutions by plugging them back in to the original equation

3*4 + 2*2 -16 = 0

16 - 16 = 0

and

3*(64/9) + 2*(8/3) - 16 = 0

192/9 - 16/3 - 16 = 0

64/3 - 16/3 - 48/3 = 0

64/3 - 64/3 = 0